Exploring Role of Good Corporate Governance in Moderating Effects of Inventory Turnover and Sales Growth on Profitability: Evidence from Indonesia's Palm Oil Companies - Norhasanah, Norhasanah; Setyadi, Djoko; Purnamasari, Ike (International Journal of Multidisciplinary Approach Research and Science, 2025)
This research is motivated by several external factors affecting the palm oil industry, including the COVID-19 pandemic, the decline in Crude Palm Oil (CPO) prices, cooking oil scarcity, and the government's CPO export ban policy, all of which have impacted the economic and operational performance of palm oil companies. This study focuses on analyzing the influence of Inventory Turnover (ITO) and Sales Growth (SG) on profitability, measured by Return on Assets (ROA), in palm oil companies listed on the Indonesia Stock Exchange during the 2019-2023 period. Furthermore, this study explores the moderating role of Good Corporate Governance (GCG), measured through the board of directors and the board of commissioners, in the relationship between the independent and dependent variables. The research employs a quantitative method with panel data regression analysis. A sample of 16 companies was selected using purposive sampling, with data sourced from financial statements and other secondary sources. Data processing was conducted using EViews 13 software. The results indicate that ITO negatively and significantly affects ROA, likely due to price volatility and market conditions. Conversely, SG demonstrates a positive and significant influence on ROA, suggesting that increased sales positively impact company profits. GCG significantly moderates the relationship between ITO and ROA, but does not significantly moderate the relationship between SG and ROA. These findings highlight the importance of applying good corporate governance principles, especially when facing uncertain economic conditions.